1986
DOI: 10.1104/pp.81.1.130
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Ethylene Biosynthesis in Avocado Fruit during Ripening

Abstract: Preclimacteric avocado (Persea americana Mill.) fruits produced very little ethylene and had only a trace amount of l-aminocyclopropane-lcarboxylic acid (ACC) and a very low activity of ACC synthase. In contrast, a significant amount of l-(malonylamino)cyclopropane-l-carboxylic acid (MACC) was detected during the preclimacteric stage. In harvested fruits, both ACC synthase activity and the level of ACC increased markedly during the climacteric rise reaching a peak shortly before the climacteric peak. The level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
21
0
1

Year Published

1989
1989
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 11 publications
7
21
0
1
Order By: Relevance
“…ACC synthase, however, remains at low control levels throughout ethylene treatment, rising only when the fruit manifests autocatalytic ethylene production at the climacteric rise. Thus the induction of ACC synthase is correlated with climacteric ethylene production, confirming earlier observations that the conversion of Sadenosylmethionine to ACC is the rate limiting step in ethylene biosynthesis in ripening avocado fruit (15,22). The failure of avocado fruit to ripen on the tree has been attributed to an inhibitory tree factor (24,27).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…ACC synthase, however, remains at low control levels throughout ethylene treatment, rising only when the fruit manifests autocatalytic ethylene production at the climacteric rise. Thus the induction of ACC synthase is correlated with climacteric ethylene production, confirming earlier observations that the conversion of Sadenosylmethionine to ACC is the rate limiting step in ethylene biosynthesis in ripening avocado fruit (15,22). The failure of avocado fruit to ripen on the tree has been attributed to an inhibitory tree factor (24,27).…”
Section: Discussionsupporting
confidence: 74%
“…ACC3 synthase and EFE are the key enzymes in the ethylene biosynthetic pathway (27), with ACC synthase activity the apparent rate limiting step (22). Whereas EFE activity has been shown to be induced by an ethylene pulse (22), in normal ripening the activity of both enzymes remains at relatively low levels until the onset of climacteric ethylene production (15). Because both pulsing and wounding (i.e.…”
mentioning
confidence: 99%
“…However, it does not seem to play a regulatory role in ethylene production at the climacteric stage. At this stage, MACC increases only slightly compared to the marked increase in the level of ACC (Sitrit et al 1986). These results suggest that the inability of most avocado cultivars to produce ethylene as long as they remain attached to the tree is mainly due to repression of ACS.…”
Section: Fruit Ripeningmentioning
confidence: 85%
“…It has been suggested that some unknown ripening inhibitor moves from the leaves or shoots to the fruit where it inhibits ethylene production and hence ripening (Burg and Burg 1964;Tingwa and Young 1975). Sitrit et al (1986) reported that inability of preclimacteric avocado fruit, to produce ethylene was due to lack of ACC as there was low activity of ACC-synthase (ACS) enzyme [catalyses the conversion o f S -a d e n o s y l m e t h i o n i n e ( S A M ) i n t o 1 -aminocyclopropane-1-carboxylic acid (ACC) during biosynthesis of ethylene]. It is also well accepted that malonylation of ACC may play a role in regulation of endogenous levels of ACC and hence ethylene production (Yang and Hoffman 1984).…”
Section: Fruit Ripeningmentioning
confidence: 99%
See 1 more Smart Citation